The crystal structure of isopenicillin N synthase with a dipeptide substrate analogue. - Daruzzaman, A; Clifton, I; Adlington, R; Baldwin, J; Rutledge, P (2013)
Isopenicillin N synthase (IPNS) converts its linear tripeptide substrate δ-L-α-aminoadipoyl-L-cysteinyl-D-valine (ACV) to bicyclic isopenicillin N (IPN), the key step in penicillin biosynthesis. Solution-phase incubation experiments have shown that IPNS will accept and oxidise a diverse array of substrate analogues, including tripeptides that incorporate L-homocysteine as their second residue, and tripeptides with truncated side-chains at the third amino acid such as δ-L-α-aminoadipoyl-L-cysteinyl-D-α-aminobutyrate (ACAb), δ-L-α-aminoadipoyl-L-cysteinyl-D-alanine (ACA) and δ-L-α-aminoadipoyl-L-cysteinyl-glycine (ACG). However IPNS does not react with dipeptide substrates. To probe this selectivity we have crystallised the enzyme with the dipeptide δ-L-α-aminoadipoyl-L-homocysteine (AhC) and solved a crystal structure for the IPNS:Fe(II):AhC complex to 1.40 Å resolution. This structure reveals an unexpected mode of peptide binding at the IPNS active site, in which the homocysteinyl thiolate does not bind to iron. Instead the primary mode of binding sees the homocysteinyl carboxylate coordinated to the metal, while its side-chain is oriented into the region of the active site normally occupied by the benzyl group of protein residue Phe211.